Bioecological features of Penicillium aurantiogriseum Dierckx (Experimental biology, 2016)
Under the influence of fungi affecting vegetables, with decreased yield and reduced storage period every year. Everyone knows the practical importance of studying the biological and ecological features of species and innovative methods for the determination of species of pathogenic fungi. There are given the results of molecular genetic and morphological study of the pathogen species of fungi green mold of onion (Allium cepa L.). When determining the taxonomic place morphological features are often giving the inaccurate result. For this purpose the identification of plant pathogenic Penicillium aurantiogriseum produced by Polymerase Chain Reaction (PCR). NS1 and NS4 primers were used to determine the gene encoding 18S rRNA. When determining the genetic sequence and within transcribed spacer 5.8S RNA encoding gene were used primers ITS1 and ITS4. For amplification of D1 / D2 domain of the gene 26S primers were used rRNA NL-1 and NL-4. They were made phylogenetic analysis of connection to cognate strains of microorganisms in comparison of the nucleotide sequences obtained by DNA sequencing. As a result of sequencing of the strain was defined views. Additionally performed studies to determine the macro- and microscopic features micromorphological strain.
Keywords: species of fungi; DNА; RNA; PCR; sequencing; Penicillium aurantiogriseum Dierckx.